Headache in the adult population of Cameroon: prevalence estimates and demographic associations from a cross-sectional nationwide population-based study - Callixte Kuate Tegueu; Anastase Dzudie Tamdja; Franklin Kom; Blaise Forgwa Barche; Peter Ebasone; Mélanie Magnerou; Paul Mbonda; Jacques Doumbe; Andreas Husøy; Hallie Thomas; Timothy J. Steiner (The Journal of Headache and Pain, 2024)
Abstract Background Knowledge of headache prevalence, and the burdens attributable to headache disorders, remains incomplete in sub-Saharan Africa (SSA): reliable studies have been conducted only in Zambia (southern SSA) and Ethiopia (eastern SSA). As part of the Global Campaign against Headache, we investigated the prevalence of headache in Cameroon, in Central SSA. Methods We used the same methodology as the studies in Zambia and Ethiopia, employing cluster-randomized sampling in four regions of Cameroon, selected to reflect the country’s geographic, ethnic and cultural diversities. We visited, unannounced, randomly selected households in each region, and randomly selected one adult member (aged 18–65 years) of each. Trained interviewers administered the Headache-Attributed Restriction, Disability and Impaired Participation (HARDSHIP) structured questionnaire, developed by an international expert consensus group and translated into Central African French. Demographic enquiry was followed by diagnostic questions based on ICHD-3 criteria. Results Headache was a near-universal experience in Cameroon (lifetime prevalence: 94.8%). Observed 1-year prevalence of headache was 77.1%. Age- and gender-adjusted estimates were 76.4% (95% confidence interval: 74.9–77.9) for any headache, 17.9% (16.6–19.3) for migraine (definite + probable), 44.4% (42.6–46.2) for tension-type headache (TTH; also definite + probable), 6.5% (5.7–7.4) for probable medication-overuse headache (pMOH) and 6.6% (5.8–7.6) for other headache on ≥ 15 days/month (H15 +). One-day prevalence (“headache yesterday”) was 15.3%. Gender differentials were as expected (more migraine and pMOH among females, and rather more TTH among males). pMOH increased in prevalence until age 55 years, then declined somewhat. Migraine and TTH were both associated with urban dwelling, pMOH, in contrast, with rural dwelling. Conclusions Headache disorders are prevalent in Cameroon. As in Zambia and Ethiopia, estimates for both migraine and TTH exceed global mean estimates. Attributable burden is yet to be reported, but these findings must lead to further research, and measures to develop and implement headache services in Cameroon, with appropriate management and preventative strategies.